2007
DOI: 10.1146/annurev.anthro.34.081804.120633
|View full text |Cite
|
Sign up to set email alerts
|

Sociophonetics

Abstract: Investigators have recently made impressive progress in multiple areas of sociophonetics. One area is the use of increasingly sophisticated phonetic analysis, which is demonstrating that very fine phonetic detail is used for the construction of social identity. A second area is the use of ethnographic approaches, which enable researchers to break free from using traditional social categories that may not be relevant for a particular group of speakers, and to investigate in depth the social meaning of particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 39 publications
2
48
0
4
Order By: Relevance
“…This was followed by an open-ended item in which the participants could explain their choice. These two items were included, first, to provide a specific real-life social context that would have immediate significance for our participants (Coupland 2007;Hay and Drager 2007), and, second, to ensure the focus on the EFL teaching perspective which was central to our investigation. This also enabled us to compare the participants' attitudes expressed through semantic differential scales to their choice of varieties considered appropriate for EFL teaching, and thus pinpoint their idea of what the EFL teacher "should sound like".…”
Section: Methodology and Proceduresmentioning
confidence: 99%
“…This was followed by an open-ended item in which the participants could explain their choice. These two items were included, first, to provide a specific real-life social context that would have immediate significance for our participants (Coupland 2007;Hay and Drager 2007), and, second, to ensure the focus on the EFL teaching perspective which was central to our investigation. This also enabled us to compare the participants' attitudes expressed through semantic differential scales to their choice of varieties considered appropriate for EFL teaching, and thus pinpoint their idea of what the EFL teacher "should sound like".…”
Section: Methodology and Proceduresmentioning
confidence: 99%
“…Recent research using experimental methodologies has shown that social and phonetic information are linked in the mind; the social information that gets attributed to a speaker can be infl uenced by altering which phonetic variants perceivers are exposed to (Campbell-Kibler 2007). Despite the advantages of both, there is little work which combines experimental methods with an ethnographic approach (Hay and Drager 2007). Combining these methods provides the opportunity to have an ethnographically informed interpretation of experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The sound symbolic value with which clicks were charged in certain copied Khoisan source words or the social role they played in terms of identity-marking may have favoured their further spread in the vocabulary of the SWB languages, either through the insertion of clicks in existing Bantu words or through click-bearing neologisms. It is known from studies in sociophonetics that even the most minute phonetic differences may be used to express social meaning (Hay and Drager 2007). Though this contrasts with many modern-day interactions between Bantu speakers and Khoisan speakers, the embracing of foreign linguistic features could suggest that speakers of SWB languages once valued Khoisan origins and positively identified with these.…”
Section: Discussionmentioning
confidence: 99%